The role of the complement system in Multiple Sclerosis: A review - Saez-Calveras, Nil; Stuve, Olaf (Frontiers in Immunology, 2022)
The complement system has been involved in the pathogenesis of multiple neuroinflammatory and neurodegenerative conditions. In this review, we evaluated the possible role of complement activation in multiple sclerosis (MS) with a focus in progressive MS, where the disease pathogenesis remains to be fully elucidated and treatment options are limited. The evidence for the involvement of the complement system in the white matter plaques and gray matter lesions of MS stems from immunohistochemical analysis of post-mortem MS brains, in vivo serum and cerebrospinal fluid biomarker studies, and animal models of Experimental Autoimmune Encephalomyelitis (EAE). Complement knock-out studies in these animal models have revealed that this system may have a “double-edge sword” effect in MS. On the one hand, complement proteins may aid in promoting the clearance of myelin degradation products and other debris through myeloid cell-mediated phagocytosis. On the other, its aberrant activation may lead to demyelination at the rim of progressive MS white matter lesions as well as synapse loss in the gray matter. The complement system may also interact with known risk factors of MS, including as Epstein Barr Virus (EBV) infection, and perpetuate the activation of CNS self-reactive B cell populations. With the mounting evidence for the involvement of complement in MS, the development of complement modulating therapies for this condition is appealing. Herein, we also reviewed the pharmacological complement inhibitors that have been tested in MS animal models as well as in clinical trials for other neurologic diseases. The potential use of these agents, such as the C5-binding antibody eculizumab in MS will require a detailed understanding of the role of the different complement effectors in this disease and the development of better CNS delivery strategies for these compounds.